Diffusion in the corpus callosum predicts persistence of clinical symptoms after mild traumatic brain injury, a multi-scanner study - Asturias, Alexander; Knoblauch, Thomas; Rodriguez, Alan; Vanier, Cheryl; Le Tohic, Caroline; Barrett, Brandon; Eisenberg, Matthew; Gibbert, Rachelle; Zimmerman, Lennon; Parikh, Shaunaq; Nguyen, Anh; Azad, Sherwin; et al. (Frontiers in Neuroimaging, 2023)
Mild traumatic brain injuries (mTBIs) comprise 80% of all TBI, but conventional MRI techniques are often insensitive to the subtle changes and injuries produced in a concussion. Diffusion tensor imaging (DTI) is one of the most sensitive MRI techniques for detection of trauma induced changes. The corpus callosum (CC) is one of the most studied fiber tracts in TBI and mTBI, but comprehensive post-mTBI symptom relationship has not fully been explored. This is a retrospective observational study of how quantitative DTI data of the CC and its sub-regions may relate to clinical presentation of symptoms and timing of resolution of symptoms in patients diagnosed with uncomplicated mTBI. DTI and clinical data were obtained retrospectively from 446 civilian patients. From patient medical charts, presentation and improvment of post-concussive symptoms (headache, balance issues, cognitive deficits, fatigue, anxiety, depression, and emotional lability) were obtained via retrospective chart review. FA values from the total CC, genu, mid-body, and splenium were hand traced on Olea Sphere v3.0 SP12. DTI data was obtained from 8 different 3T MRI scanners and harmonized via ComBat harmonization. Statistical models used to explore the association between regional Fractional Anisotropy (FA) values and symptom presentation and time to symptom resolution were logistic regression and interval-censored semi-parametric Cox proportional hazard models, respectively. Subgroups related to age and timing of first scan were also analyzed. Patients with the highest FA in the total CC (p=0.01), anterior CC (p<0.01), and mid-body CC (p=0.03), but not the posterior CC (p=0.91) recovered faster from post-concussive cognitive deficits. Patients with the highest FA in the posterior CC recovered faster from depression (p=0.04) and emotional lability (p=0.01). There was no evidence that FA in the CC or any of its sub-regions was associated with symptom presentation or with time to resolution of headache, balance issues, fatigue, or anxiety. Patients with mTBI under 40 had higher FA in the CC and the anterior and mid-body subregions (but not the posterior subregion: p=1.00) compared to patients 40 or over (p<0.01). There was no evidence for differences in symptom presentation based on loss of consciousness (LOC) or sex (p>0.18).